Measuring the Impact of Health on Economic Growth Using Pooling Data in Regions of Asia: Evidence From a Quantile-On-Quantile Analysis - Wu, Cheng-Feng; Chang, Tsangyao; Wang, Chien-Ming; Wu, Tsung-Pao; Lin, Meng-Chen; Huang, Shian-Chang (Frontiers in Public Health, 2021)
Health improvement has become a significant social priority since a moderately good human capital condition improves the workforce’s abilities, efficiency, and quality of life. A rapid increase in healthcare expenditure is a trend in major developing and developed countries; however, healthcare expenditure widely varies among Asian countries. Asian countries contribute a significant amount of output to economic development worldwide. The statistical test power is more efficient for the pooling of national data than individual national data because of the value economic and trade integration of regional nations. This is the first study that applies the quantile-on-quantile approach to investigate the influence of the quantiles of healthcare on the quantiles of the economy’s growth for pooling forty countries in the Asian region. As the quantile of healthcare expenditure increases in the countries, the impact of healthcare expenditure on the economy’s growth does not guarantee an increase. The positive and negative effects of healthcare expenditure on developing the economic relationship will repeatedly occur when the quantiles of the economy’s growth increase in the countries. One implication is that the governments should account for the problem such as corruption, bureaucracy, underinvestment, and inefficiency in health-related resource utilization.